2013
DOI: 10.1097/nnr.0b013e31827bf533
|View full text |Cite
|
Sign up to set email alerts
|

African American Men and Women’s Attitude Toward Mental Illness, Perceptions of Stigma, and Preferred Coping Behaviors

Abstract: Background Although research focused on African Americans with mental illness has been increasing, few researchers have addressed gender and age differences in beliefs, attitudes, and coping. Objective To examine African Americans' beliefs about mental illness, attitudes toward seeking mental health services, preferred coping behaviors, and whether these variables differ by gender and age. Method An exploratory, cross-sectional survey design was used. Participants were 272 community-dwelling African Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
168
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(182 citation statements)
references
References 27 publications
(56 reference statements)
10
168
4
Order By: Relevance
“…Mackenzie, Gekoski, & Knox, 2006; ten Have et al, 2010) and being Caucasian (Ward, Wiltshire, Detry, & Brown, 2013) was correlated with more favourable attitudes. Young adults were reported to have less positive attitudes towards seeking professional help than older adults (Gonzalez, Alegria, & Prihoda, 2005; Robb, Haley, Becker, Polivka, & Chwa, 2003).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Mackenzie, Gekoski, & Knox, 2006; ten Have et al, 2010) and being Caucasian (Ward, Wiltshire, Detry, & Brown, 2013) was correlated with more favourable attitudes. Young adults were reported to have less positive attitudes towards seeking professional help than older adults (Gonzalez, Alegria, & Prihoda, 2005; Robb, Haley, Becker, Polivka, & Chwa, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…IASMHS has been used to investigate attitudes in college students (Mackenzie et al, 2004; Mojaverian, Hashimoto, & Kim, 2012; Wahto & Swift, 2016; Yousaf, Popat, & Hunter, 2015), adolescents (Munson, Floersch, & Townsend, 2010), older adults (Kessler, Agines, & Bowen, 2014), psychotherapy clients (Elkins, Swift, & Campbell, 2016), and specific ethnic groups: Alaska natives (Freitas-Murrell & Swift, 2015), South Asians (Loya, Reddy, & Hinshaw, 2010), Chinese immigrants (Tieu & Konnert, 2014), and African Americans (Ward et al, 2013; Watson & Hunter, 2015). Only a few studies screened for mental disorders (Mackenzie et al, 2006; Mesidor & Sly, 2014; Munson et al, 2010; Troeung, Gasson, & Egan, 2015; Ward et al, 2013; Watson & Hunter, 2015) and intentions to (or actual) mental health service use (Freitas-Murrell & Swift, 2015; James & Buttle, 2008; Martin & Howe, 2016; Tieu & Konnert, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may reflect a true difference in eating behaviors across racial and ethnic groups or alternatively, or it may reflect a downward bias in reporting due to stigma around mental health issues in the African-American community. 37 Compared with Caucasians, both African-Americans and Hispanics were more likely to report cognitive restraint independently of BMI. These interesting racial differences may be important to consider in the context of obesity treatment and merit exploration in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…Ward, Wiltshire, Detry, and Brown (2013) found among a sample of 272 African American men (n = 158) and women (n = 114) between the ages of 25 and 72, that participants were reluctant to disclose psychological problems and were very concerned about the stigma associated with a mental illness, but were somewhat open to seeking mental health services. This finding is in contrast with previous literature that suggested that African Americans tend to have negative views toward mental health treatment-seeking (Gary, 2005).…”
Section: Structural Stigmamentioning
confidence: 99%